The effects of needle deformation during lumbar puncture - Ozdemir, Hasan Huseyin; Demir, Caner F.; Varol, Sefer; Arslan, Demet; Yildiz, Mustafa; Akil, Esref (Wolters Kluwer Medknow Publications, 2015)
Objective: The aim of this study is to assess deformation of the tip and deflection from the axis of 22-gauge Quincke needles when they are used for diagnostic lumbar puncture (LP). Thus, it can be determined whether constructional alterations of needles are important for predicting clinical problems after diagnostic LP. Materials and Methods: The 22-gauge Quincke needles used for diagnostic LP were evaluated. A specially designed protractor was used for measurement and evaluation. Waist circumference was measured in each patient. Patients were questioned about headaches occurring after LP. Results: A total of 115 Quincke-type spinal needles used in 113 patients were evaluated. No deflection was detected in 38 (33.1%) of the needles. Deflection between 0.1 degrees and 5 degrees occurred in 43 (37.3%) of the needles and deflection >= 5.1 degrees occurred in 34 patients (29.6%). Forty-seven (41.5%) patients experienced post lumbar puncture headache (PLPH) and 13 (11.5%) patients experienced intracranial hypotension (IH). No statistically significant correlation between the degree of deflection and headache was found (P > 0.05). Epidural blood patch was performed for three patients. Deformity in the form of bending like a hook occurred in seven needles and IH occurred in six patients using these needles. Two of the needles used in three patients requiring blood patch were found to be bent. Conclusion: Deformation of needles may increase complications after LP. Needle deformation may lead to IH. In case of deterioration in the structure of the needle, termination of the puncture procedure and the use of a new needle could reduce undesirable clinical consequences, especially IH.
Keywords: Headache; intracranial hypotension; Lumbar puncture; needle deflection